2015
DOI: 10.1002/adhm.201500450
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles for Transdermal Biosensing: Current Picture and Future Direction

Abstract: A novel trend is rapidly emerging in the use of microneedles, which are a miniaturized replica of hypodermic needles with length-scales of hundreds of micrometers, aimed at the transdermal biosensing of analytes of clinical interest, e.g., glucose, biomarkers, and others. Transdermal biosensing via microneedles offers remarkable opportunities for moving biosensing technologies and biochips from research laboratories to real-field applications, and envisages easy-to-use point-of-care microdevices with pain-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(132 citation statements)
references
References 129 publications
0
126
0
Order By: Relevance
“…The heated solution was poured into a transparent polystyrene cube box (2.5 × 2.5 × 2.5 cm, Ted Pella, Redding, CA), and the box was cooled in a refrigerator (5 °C) for 20 min for curing. The compression modulus of the gel was 22.9 kPa, similar to typical Young's modulus of dermis layer (10–30 kPa) . A chicken muscle tissue was used as a fibrous tissue model.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The heated solution was poured into a transparent polystyrene cube box (2.5 × 2.5 × 2.5 cm, Ted Pella, Redding, CA), and the box was cooled in a refrigerator (5 °C) for 20 min for curing. The compression modulus of the gel was 22.9 kPa, similar to typical Young's modulus of dermis layer (10–30 kPa) . A chicken muscle tissue was used as a fibrous tissue model.…”
Section: Methodsmentioning
confidence: 92%
“…The compression modulus of the gel was 22.9 kPa, similar to typical Young's modulus of dermis layer (10-30 kPa). [23] A chicken muscle tissue was used as a fibrous tissue model. The chicken was cut into specimens with 13 mm width, 15 mm length, and 11 mm thickness using a razor blade.…”
Section: Methodsmentioning
confidence: 99%
“…This is what happened to the micro-and nanotechnologies that have revolutionized consumer electronics and telecommunications. [10,11] In these papers, the MNs are classified on the basis of their material (silicon, metal, glass, ceramic, polymer), shape (pyramidal, conical, solid, hollow, coated), bio-features (dissolvable, degradable, biocompatible, bioresponsive), and finally fabrication process (multistep, single step). [4] The convergence of such different fields of knowledge has generated a multitude of similar devices grouped under the single name of microneedles, which can be very different in terms of the materials used, fabrication procedures, and features exploited.…”
Section: One Device Several Technologiesmentioning
confidence: 99%
“…[5][6][7][8][9] Exhaustive reviews of silicon-based MN arrays and other categories of MN-based devices can be found in recent papers by Ventrelli et al and Ma et al, respectively. [10,11] In these papers, the MNs are classified on the basis of their material (silicon, metal, glass, ceramic, polymer), shape (pyramidal, conical, solid, hollow, coated), bio-features (dissolvable, degradable, biocompatible, bioresponsive), and finally fabrication process (multistep, single step). Beyond the classification of the MN patches, the working principle is always the same: the aim is to control the time and quantity of drug release and delivery through the skin without pain by tuning the physical, structural, or chemical characteristics of the device.…”
Section: One Device Several Technologiesmentioning
confidence: 99%
See 1 more Smart Citation